Introduction to public administration - Bean, Idris (New York, NY, USA Clanrye International, 2023)
Public administration primarily studies the implementation of government policies. Some of the fundamental branches of public administration are organization theory, ethics, policy analysis, public budgeting and human resource management. Organization theory studies the structure of governmental entities. Ethics in public administration serves as a normative approach to decision making. Policy analysis functions as an empirical approach to decision making. The allocation of scarce resources among unlimited demands is conducted within public budgeting. There are numerous decision making models which are studied within this field such as Niskanen's budget-maximizing and Dunleavy's bureau-shaping model. This book is a valuable compilation of topics, ranging from the basic to the most complex theories and principles in the field of public administration. It aims to shed light on some of the unexplored aspects of this field. This textbook will serve as a valuable source of reference for those interested in this field.
Chapter 1: WHAT IS PUBLIC ADMINISTRATION?: Principles of public administration -- Administrative culture -- Management models in the public administration -- Public administration theory -- Administrative reforms.

Chapter 2: FUNDAMENTAL ASPECTS OF PUBLIC ADMINISTRATION: Administrative law -- Administrative discretion -- Public interest -- Decentralisation -- Advocacy evaluation -- Public service -- Civil service -- Bureaucracy.

Chapter 3: PUBLIC POLICIES: Agricultural policy -- Commercial policy -- Cultural policy -- Domestic policy -- Government economic policy -- Foreign policy -- Policy monitoring -- Policy alienation.

Chapter 4: SUB-FIELDS OF PUBLIC ADMINISTRATION: Organizational theory -- Public sector ethics -- Policy analysis -- Public budgeting -- Human resource management in public administration.

Chapter 5: DECISION-MAKING MODELS.

Chapter 6: UNDERSTANDING E-GOVERNANCE: E-government -- E-governance -- Transformational government -- E-rulemaking -- E-participation -- E-services.

Chapter 7: PERSONNEL AND FINANCIAL ADMINISTRATION: Personnel administration -- Financial administration.
Includes bibliographical references and index.
Keywords: Public administration